Evaluating the biological variability of blood‐based biomarkers for use in clinical trials. (20th December 2022) - Trombetta, Bianca A.; Allen, Shona W.; El‐Mufti, Leena H.; Riley, Misha M.; Ramirez, Christopher E.; Weik, Molly; Carlyle, Becky C.; Kivisäkk, Pia; Arnold, Steven E.
Abstract: Background: Blood‐based biomarkers offer the possibility of inexpensive, minimally invasive, and accessible diagnostic tools for Alzheimer's Disease (AD). In the context of clinical trials, these biomarkers hold promise for subject stratification and monitoring the effects of therapeutic interventions. The day‐to‐day variability of these measures must be robustly characterized to determine which blood‐based biomarkers would be the most sensitive for detecting treatment‐related responses. In this study we evaluate biomarker performance in plasma and identify the most reliable candidates for clinical trials. Method: EDTA plasma samples were collected from healthy controls (n=20, 50% female, mean age 56.03 ± 9.43 years) at baseline, 2 weeks, and 4 weeks. Singleplex ELISA and multiplex MesoScale Discovery (MSD) immunoassays were used to measure over 25 biomarkers that were selected for their relevance to dysregulated processes in AD and previously validated in cerebrospinal fluid (CSF). Technical performance was assessed by calculating intra‐ and inter‐plate coefficients of variation (CVs), analyzing dilution linearity, and evaluating freeze‐thaw stability. Biological intra‐individual variability was examined by calculating a biotemporal CV for each subject across the three timepoints. Results: Most biomarkers were quantifiable in plasma and exhibited technical performance within our thresholds (intra‐ and inter‐plate CV < 15%). The biomarkers exhibited a range of freeze‐thaw stability, with mean CVs from 5.2% for Adiponectin, a regulator of glucose metabolism, to 30.2% for GRP78, an ER chaperone protein. Plasma levels were relatively stable across time (biotemporal CV < 20%) for several biomarkers, including 24‐OHC, VEGF‐D, Flt‐1, PlGF, sST2, and sTREM2. Several proteins exhibited significant variability over time (biotemporal CV > 20%), such as 8‐OHdG, GRP78, and YKL‐40. Conclusion: Key metabolic, vascular, and inflammatory biomarkers were reliably measurable in the plasma of healthy individuals. Several markers exhibited substantial variability over a 2‐4 week time period, which should be taken into consideration when selecting appropriate markers for assessing drug‐target engagement. Designing future clinical trials with multiple baseline visits will allow us to establish biological variability metrics for each individual's biomarker levels, providing greater confidence in determining treatment effects. Evaluating biomarker stability in other large‐scale subject populations will be necessary to best inform blood‐based biomarker selection for clinical trials.